2015
DOI: 10.1111/odi.12317
|View full text |Cite
|
Sign up to set email alerts
|

Desipramine inhibits salivary Ca2+ signaling and aquaporin translocation

Abstract: These results imply that desipramine blocks muscarinic and histamine receptor-mediated Ca(2+) signaling and the subsequent translocation of aquaporin-5 in human salivary gland cells, suggesting a novel mechanism for the xerogenic effects of desipramine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…To determine the effect of MβCD on aquaporins, we analyzed the expression level of AQP5 via GFP intensity in the membrane fraction. In a previous study, we confirmed that 20 min of carbachol treatment was optimal for confirming activity-dependent AQP5 translocation [ 28 ]. We prepared the membrane fraction of HSG cells and analyzed the level of AQP5 in comparison with Na + /K + exchanger, a membrane-enriched protein.…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…To determine the effect of MβCD on aquaporins, we analyzed the expression level of AQP5 via GFP intensity in the membrane fraction. In a previous study, we confirmed that 20 min of carbachol treatment was optimal for confirming activity-dependent AQP5 translocation [ 28 ]. We prepared the membrane fraction of HSG cells and analyzed the level of AQP5 in comparison with Na + /K + exchanger, a membrane-enriched protein.…”
Section: Resultssupporting
confidence: 78%
“…The cytosolic free Ca 2+ concentration ([Ca 2+ ] i ) was determined using the fluorescent Ca 2+ indicator fura-2/AM, as previously described [ 27 , 28 ]. Briefly, the cell suspension was incubated in fresh medium containing fura-2/AM (4 µM) for 60 min at 37 °C with continuous stirring.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The translocation of aquaporin‐5 into the plasma membrane is one of the cellular mechanisms of water secretion in salivary gland cells, HSG cells transfected with GFP‐tagged aquaporin‐5 have been used to analyze the amount of aquaporin‐5 translocated with Na + /K + ‐ATPase as a membrane protein marker . We monitored the bradykinin‐mediated modulation of aquaporin‐5 translocation in HSG cells transfected with GFP‐tagged aquaporin‐5 using the membrane protein marker, Na + /K + ‐ATPase.…”
Section: Resultsmentioning
confidence: 99%